2008
DOI: 10.1890/08-0267.1
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐herbivore Protection by Mutualistic Spiders and the Role of Plant Glandular Trichomes

Abstract: Although specific associations between spiders and particular types of plants have been reported for several taxonomic groups, their consequences for spiders and plants are still poorly understood. The most common South American lynx spiders, Peucetia flava and P. rubrolineata, live strictly associated with various plant species that have glandular trichomes.To understand more about these spider-plant relationships, we investigated the influence of the spiders on the fitness of a neotropical glandular shrub (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
98
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(118 citation statements)
references
References 43 publications
4
98
1
3
Order By: Relevance
“…The main and bestknown defense mechanism against herbivory is direct defense, in which the plants have secondary compounds in several structures that make the herbivores' ability to exploit these plants more difficult (Coley & Kursar 1996;Cortesero et al 2000). However, plants also have indirect defenses by the third trophic level, particularly predator insect and parasitic wasps and flies (parasitoids), which are known to protect plants against herbivory (Rico-Gray & Oliveira 2007;Romero et al 2008). This indirect and biotic defense is usually induced, where the plant releases volatile and/or nutritive substances that attract predators and herbivore parasitoids (Kessler & Baldwin 2001;Sabelis et al 2001;Heil 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The main and bestknown defense mechanism against herbivory is direct defense, in which the plants have secondary compounds in several structures that make the herbivores' ability to exploit these plants more difficult (Coley & Kursar 1996;Cortesero et al 2000). However, plants also have indirect defenses by the third trophic level, particularly predator insect and parasitic wasps and flies (parasitoids), which are known to protect plants against herbivory (Rico-Gray & Oliveira 2007;Romero et al 2008). This indirect and biotic defense is usually induced, where the plant releases volatile and/or nutritive substances that attract predators and herbivore parasitoids (Kessler & Baldwin 2001;Sabelis et al 2001;Heil 2008).…”
Section: Introductionmentioning
confidence: 99%
“…These structures perform important biological functions, such as discouraging herbivory, attracting pollinators, and maintaining a boundary layer (Nihoul, 1993;Van Dam and Hare, 1998;Kennedy, 2003;Moyano et al, 2003;Simmons and Gurr, 2005;Liu et al, 2006;Horgan et al, 2007;Gonzalez et al, 2008;Romero et al, 2008;Nonomura et al, 2009;Kang et al, 2010). Many of these functions are the result of the specialized nature of glandular trichomes (glands) as sites for the synthesis and storage of biologically active specialized metabolites (Alonso et al, 1992;Antonious, 2001;Iijima et al, 2004;Siebert, 2004;Deschamps et al, 2006;Nagel et al, 2008;Wang et al, 2008;Biswas et al, 2009;Sallaud et al, 2009).…”
mentioning
confidence: 99%
“…The presence of spiders on inflorescences may easily affect the plant reproductive success. Spiders can prey on phytophagous harmful to the floral structures and consequently reduce their abundance, a fact that lead to an increase in plant reproductive success [3]. Indeed, several studies have demonstrated that spiders may play an effective role in biological pest control [2,38].…”
Section: Discussionmentioning
confidence: 99%
“…They frequently use plants as substrate to forage and represent one of the main predators that control phytophagous arthropods in natural and agricultural systems [2,3]. Furthermore, spiders also represent a key-assemblage to plants, since they play a potentially critical role over the dynamics of local trophic networks [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation